Penguatan kapasitas teknik dasar atlet muda melalui program pelatihan passing atas di klub bolavoli Satria Sejati Semarang - M. Dandy Aryadi; Didik Cahyono (CV Rezki Media, 2025)
Overhead passing skills are a fundamental technique in volleyball that often poses a challenge for young athletes, including those at the Satria Sejati Volleyball Club in Semarang. Based on initial observations, most athletes struggle to control the direction of the ball, maintain the power of their push, and keep a stable hand position. This community service activity aims to enhance the overhead passing skills of young athletes by applying a practical and easy-to-implement wall passing training method. The activity was conducted over a period of two months, with training sessions held three times a week, involving 24 athletes aged 13–17 years. The implementation method employed an experimental approach with a pretest–posttest design, where data were analyzed descriptively by comparing mean differences. The results showed an increase in passing ability from an average of 35.75 to 39.41, with a difference of 3.66 points. This improvement reflects the effectiveness of wall training in improving ball control, pushing power, and bounce accuracy. This activity also had a positive impact on increasing athlete motivation, while strengthening coaches' capacity to continuously apply scientifically based training models in the club environment.